Perhubungan antara prinsip-prinsip TQM dengan prestasi organisasi pendidikan: Satu kajian empirikal dalam sektor pendidikan tinggi awam di Malaysia - Lim, Kong Teong; Yusoff, Rushami Zien; Ahmad, Zainal Ariffin; Tang, Swee Mei (Universiti Utara Malaysia, 2006)
This study investigates the relationship between principles of total quality management (TQM) and educational organisation outcome with respect to student satisfaction and student academic achievement. The survey approach was used in this study and the time horizon was cross-sectional. The survey was carried out in 100 educational departments selected randomly from 10 public universities in Malaysia. The final number of participants for this study was 85 educational departments. The sample size comprised about 70% of the total population. The study hypotheses were tested using correlational and linear regression analyses. The results supported all the hypotheses posited for the study, suggesting that educational organisations can benefit from TQM principles. Pearson-r correlations indicated that all of the TQM principles have significant correlations with student satisfaction and student academic achievement variables. Principle component analysis and simple linear regression were carried out to reduce the possible effects of multi-collinearity and to determine the relationship of the variables, and the results indicated that TQM principles explained a significant percentage of the variance in student satisfaction and student academic achievement variables.